Bridging the information gap: What are the impacts of EPCs on Prague's residential market selling prices? - Tomáš Podškubka; Barbora Rýdlová; Josef Arlt (Financial Internet Quarterly, 2025)
It is assumed that energy performance certificates (EPC) can promote energy efficiency, increase property values, and improve market liquidity by providing trustworthy energy performance information. This article will provide a comprehensive study of the impact of EPCs on the residential selling prices in Prague, the capital of the Czech Republic. For the analysis, the original dataset was extracted from the publicly accessible sreality.cz portal. The hedonic regression model was applied to evaluate how the EPC influences the selling price of apartments in Prague. The regression analysis results are entirely in line with the analyzed current literature. EPC ratings have been proven to significantly affect the selling price in Prague and several other locations. In the most affluent locations of Prague, i.e., typically historical locations, the EPC ratings have not proved to be a statistically significant price factor because these locations suffer from excess demand and limited supply of properties.
Keywords: C31; Q40; R21; R31; 330; Czech Housing Market; Energy Efficiency; Energy Performance Certificate; Hedonic Regression Model; Residential Properties